1993
DOI: 10.1002/mus.880160205
|View full text |Cite
|
Sign up to set email alerts
|

Plasma carnitine insufficiency and effectiveness of L‐carnitine therapy in patients with mitochondril myopathy

Abstract: Plasma carnitine "insufficiency," (plasma esterified carnitine to free carnitine ratio above 0.25) was found in 21 of 48 (43.8%) patients with mitochondrial myopathy, of whom 4 also showed both total and free carnitine deficiencies in plasma. In addition, plasma levels of SCAC and LCAC were higher in patients with mitochondrial myopathy than in controls (P < 0.001 and P < 0.01, respectively). Patients diagnosed as having plasma carnitine insufficiency or deficiency were treated with L-carnitine (50-200 mg/kg p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 18 publications
4
42
1
3
Order By: Relevance
“…Similar normal values were reported in an article describing patients suffering from mitochondrial myopathy based on the clinical findings of muscle weakness and specific histopathologic features found on muscle biopsy [19]. That article indicated that carnitine levels below their normal range were associated with cardiomyopathy, muscle weakness and related muscle pathology that improved with carnitine supplementation [19]. Low free carnitine was found in (11/40) 28% of our study subjects.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar normal values were reported in an article describing patients suffering from mitochondrial myopathy based on the clinical findings of muscle weakness and specific histopathologic features found on muscle biopsy [19]. That article indicated that carnitine levels below their normal range were associated with cardiomyopathy, muscle weakness and related muscle pathology that improved with carnitine supplementation [19]. Low free carnitine was found in (11/40) 28% of our study subjects.…”
Section: Resultssupporting
confidence: 88%
“…These results were compared to values established for healthy adults in the clinical laboratory of All Children's Hospital, which is CAP certified and participates in their Proficiency Testing program. These results are similar to those reported in the literature [19]. None of these subjects had any clinical evidence of cardiovascular, renal or liver disease.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…It was found that daily administrations of 2 -3 g of LC led to blood carnitine concentrations superior to normal levels (Bach et al, 1983;Baker et al, 1993;Brass et al, 2001). Rapid recovery of symptomatic plasma carnitine deficiency is obtained within 10 days by either oral high-dose treatment (3 -4 g) in a single administration or by more prolonged therapy (Bizzi et al, 1978;Campos et al, 1993). Mucosal absoption of LC is saturated by 2 g doses and oral fractioned treatment for higher doses is required (Farper et al, 1988).…”
Section: Treatment Plan With Lcmentioning
confidence: 99%
“…Carnitine regulates the transport of fatty acids across the inner mitochondrial membrane and modulates the intracellular acy1CoA:free CoA ratio (2,3) ( Figure 1). It also enhances P-oxidation of longchain fatty acids, stimulates the respiratory chain, and interacts with membrane phospholipids (2)(3)(4)(5)(6)(7). Thus, carnitine insufficiency could produce wide metabolic derangement and impairment of muscle function.…”
mentioning
confidence: 99%